2021
DOI: 10.3389/fpubh.2021.662231
|View full text |Cite
|
Sign up to set email alerts
|

The “Vulnerability” Discourse in Times of Covid-19: Between Abandonment and Protection of Canadian Francophone Older Adults

Abstract: The Covid-19 pandemic has been particularly difficult for older Canadians who have experienced age discrimination. As the media can provide a powerful channel for conveying stereotypes, the current study aimed to explore how Canadian Francophone older adults and the aging process were depicted by the media during the first wave of the Covid-19 pandemic, and to examine if and how the media discourse contributed to ageist attitudes and behaviors. A content analysis of two French Canadian media op-eds and comment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…However, research has demonstrated that dementia does not progress in a linear fashion and, most notably, that it varies from person to person [ 35 - 37 ]. Similar stereotypes focusing on frailty and COVID-19 vulnerability among older adults have been found in public health campaigns and traditional news media [ 5 , 6 , 38 - 40 ]. These stereotypes serve to perpetuate COVID-19 stigma against older adults and people with dementia.…”
Section: Discussionsupporting
confidence: 60%
“…However, research has demonstrated that dementia does not progress in a linear fashion and, most notably, that it varies from person to person [ 35 - 37 ]. Similar stereotypes focusing on frailty and COVID-19 vulnerability among older adults have been found in public health campaigns and traditional news media [ 5 , 6 , 38 - 40 ]. These stereotypes serve to perpetuate COVID-19 stigma against older adults and people with dementia.…”
Section: Discussionsupporting
confidence: 60%
“…Indeed, Fraser et al (2020) warned of the potential negative impacts of ageist hashtags circulating on social media during the early weeks of the COVID-19 pandemic. Lagacé et al (2021) report similar concerns about the COVID-19 media discourse labelling all older adults as vulnerable people whom we must "fight for" and not "fight along with." Similarly, Stollznow (2020) describes how prejudice in ageist language perpetuates conflict between boomer and millennial generations, and in the end, impacts everyone.…”
Section: Discussionmentioning
confidence: 94%
“…Advocates in Quebec society spoke out and defended those living in LTC. Other studies found that some older adults living in the community distanced themselves from those living in a CHSLD (Lagacé et al, 2021). As social isolation grew strong among the residents of various LTC homes and certain deleterious living conditions were exposed, some individuals demonstrated their advocacy directly, with deliberate acts of kindness, while others acted indirectly, challenging the underlying ageist views that are present in the public discourse.…”
Section: Discussionmentioning
confidence: 99%